Networks and centroid metrics for understanding football - Gama, J.; Dias, G.; Couceiro, M.; Belli, R.; Vaz, V.; Ribeiro, J.; Figueiredo, A. (South African Journal for Research in Sport, Physical Education and Recreation, 2016)
This study aimed to verify the network of contacts resulting from the collective behaviour of professional football teams through the centroid method and networks as well, therebyproviding detailed information about the match to coaches and sport analysts. For this purpose, 999 collective attacking actions from two teams were analysed, including passes completed, passes received and crosses, involving a total of 2335 intra-team interactions (1160 passes and crosses performed and 1175 ball receptions). Amisco® software was used to characterisethe collective behaviour of professional football teams. The results showed that the interaction of the centroid players in the offensive phase of the gameoccurred, preferably, through the formation of vertices that were connected by links, which were mainly orchestrated by the action of centroid players. It was concluded that the interactions of the professional football teams tendedto occur preferentially on the offensive phase of the game, and the network of contacts was controlled, mainly, in ball possession, through passes performed in the central and lateral areas of the field. The herein presented findings may help coaches and sport scientists to understand better, how self-organisation emerges and how collective behaviour is orchestrated.